Mastopexy with the splitting of the upper pectoral muscle and inferior muscle flap - Sgarbi, Jerônimo Martinez; Secanho, Murilo Sgarbi [UNESP]; Sgarbi, Victória (Thieme, 2021)
■ ABSTRACT Introduction: Mastopexies are among the most performed aesthetic procedures globally but still have a high patient dissatisfaction rate. Several techniques have been described in the search for the improvement of the technique. Kahn described a technique with biplanar dissection of the pectoralis major muscle, creating a superior envelope for the prosthesis’s inclusion in this space. The modification of this, associated with Daniel’s lower flap, leads to good results, with low rates of complications. The objective is to describe the muscle splitting technique described by Kahn, performed in combination with the lower pedicle flap described by Daniel in the augmentation mastopexies. Methods: Description of the technique and retrospective analysis, through medical records, of patients submitted to this surgery at the Dr. Jerônimo Clinic, located in Ibitinga/ SP. Results: We analyzed 192 patients, with a mean age of 43 years. The procedure average time was 150 minutes. There were 21 complications, such as seroma, unaesthetic scarring, asymmetries, and epidermolysis. This technique is a therapeutic arsenal for mastopexies. It has the advantage of not presenting complications related to the total and subglandular submuscular plane. It presents the naturalness of the contour in the upper pole, absence of lateralization, and prosthesis movement. Furthermore, the association with a lower flap provides greater protection and support to the implant, reducing the chance of ptosis. Conclusion: The technique presented good results, with low rates of complications. It is evidencing a viable, safe and reproducible alternative to perform augmentation mastopexy.
Mastopexia com splitting de músculo peitoral superior e cinta muscular inferior
Keywords: Breast implants; Mama; Mammoplasty; Pectoral muscles; Plastic surgery